THE EFFECT OF GDP, FDI, AND POPULATION GROWTH ON OPEN UNEMPLOYMENT IN INDONESIA: AN ISLAMIC ECONOMIC PERSPECTIVE - Sari, Putri Wulan; Fasa, Muhammad Iqbal; Nurmalia, Gustika (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Indonesia is one of the developing countries in ASEAN. With a population of approximately 281.6 million people in 2024, Indonesia ranks as the fourth most populous country in the world. However, despite this large population, the unemployment rate in Indonesia remains relatively high. This study aims to analyze the influence of Gross Domestic Product (GDP), foreign direct investment (FDI), and population growth on open unemployment in Indonesia in both the long term and short term. The research method used is descriptive quantitative with a sample of 28 years, covering the period from 1996 to 2023. The approach applied is the Vector Error Correction Model (VECM). The results of this study show that the variables of FDI and population growth have a significant effect on open unemployment in the long term, while the GDP variable does not have a significant effect on open unemployment in the long term. In the short-term analysis, the variables of Gross Domestic Product (GDP), foreign direct investment (FDI), and population growth all have no significant effect on open unemployment, due to structural changes in the economy, investment, and demography requiring time to have a tangible impact on unemployment levels. Based on the summarized discussion, it can be concluded that the variables of Gross Domestic Product (GDP), foreign direct investment (FDI), population growth, and open unemployment can be estimated using the Vector Error Correction Model (VECM)